2020
DOI: 10.1002/tea.21630
|View full text |Cite
|
Sign up to set email alerts
|

Experiences, activities, and personal characteristics as predictors of engagement in STEM‐focused summer programs

Abstract: Out‐of‐school‐time programs for youth that are focused on STEM content are often seen as affording opportunities to increase youth engagement, interest, and knowledge in STEM domains, yet we know relatively little about how youth actually experience such programs. In this article, we explore how experiences and activities employed in the delivery of summer STEM programs are associated with youth engagement during programming, and whether youth characteristics moderate these relationships. Data were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…These results suggest that youth who do not experience science at home, do not have family members or adults who work in science, or do not have the materials at home to engage in science are less likely to feel confident in their ability to do science and are less likely to perceive science is valued by their family. Furthermore, families that engage in science activities together may be more likely to collaborate on the shared relevance of the science‐related task, and relevance has been shown to promote engagement in out‐off‐school STEM programs (Schmidt et al, 2020). These factors have roots in Archer et al's (2012) concepts of family science habitus which argues that a child's choice to engage in science is related to the support that the child receives at home for science.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that youth who do not experience science at home, do not have family members or adults who work in science, or do not have the materials at home to engage in science are less likely to feel confident in their ability to do science and are less likely to perceive science is valued by their family. Furthermore, families that engage in science activities together may be more likely to collaborate on the shared relevance of the science‐related task, and relevance has been shown to promote engagement in out‐off‐school STEM programs (Schmidt et al, 2020). These factors have roots in Archer et al's (2012) concepts of family science habitus which argues that a child's choice to engage in science is related to the support that the child receives at home for science.…”
Section: Discussionmentioning
confidence: 99%
“…It is positively associated with academic achievement in various domains, and social and emotional learning outcomes (Klem & Connell, 2004 ). Much research on engagement has been conducted in the formal learning context (Christenson et al, 2012 ; Schmidt et al, 2020 ), while recent years witness an increasing trend to employ the framework of engagement to understand learners’ learning experiences out of school (Bell et al, 2019 ; Christenson et al, 2012 ). For instance, Shernoff and Vandell ( 2007 , p. 891) conceptualized student engagement as “the simultaneous experience of concentration, interest, and enjoyment” and measured students’ engagement in after-of-school activities using the experience sampling method.…”
Section: Engagement In Self-driven Learningmentioning
confidence: 99%
“…They found that students reported higher levels of engagement when participating in after-school sport and art activities than when completing homework at programs. Schmidt et al ( 2020 ) researched how youth experiences (e.g., challenge, relevance) are associated with their engagement in summer STEM programs. They measured youth momentary engagement using four items focusing on the levels of their hard work, concentration, enjoyment, and interest and found that when the youth perceived the program activities to be more challenging and relevant and to have more affordances for their development and learning, they tended to report higher engagement (Schmidt et al, 2020 ).…”
Section: Engagement In Self-driven Learningmentioning
confidence: 99%
“…It will provide opportunities for students to make knowledge connections in ways that are familiar to them. Even if necessary, STEM learning can present experiences close to students (personal experience) and real or related to students' real-life outside of school (Schmidt et al, 2020).…”
Section: Figure 3 the Example Of Respondents' Drawing After Teaching Internshipmentioning
confidence: 99%